2008
DOI: 10.1345/aph.1l474
|View full text |Cite
|
Sign up to set email alerts
|

Scope, Completeness, and Accuracy of Drug Information in Wikipedia

Abstract: Wikipedia has a more narrow scope, is less complete, and has more errors of omission than the comparator database. Wikipedia may be a useful point of engagement for consumers, but is not authoritative and should only be a supplemental source of drug information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(123 citation statements)
references
References 20 publications
1
122
0
Order By: Relevance
“…Wikipedia is apparently less credible than some other online reference resources (Kubiszewski et al 2011;Rector 2008) and seems to provide inaccurate, incomplete and poorly referenced information for some topics (Clauson et al 2008;Lavsa et al 2011). Its quality also seems to vary between language editions (see, for instance, Cabrera-Hernández 2013).…”
Section: Wikipedia Mentionsmentioning
confidence: 99%
“…Wikipedia is apparently less credible than some other online reference resources (Kubiszewski et al 2011;Rector 2008) and seems to provide inaccurate, incomplete and poorly referenced information for some topics (Clauson et al 2008;Lavsa et al 2011). Its quality also seems to vary between language editions (see, for instance, Cabrera-Hernández 2013).…”
Section: Wikipedia Mentionsmentioning
confidence: 99%
“…11 Another of the most obvious concerns is that someone may vandalize a wiki by posting inaccurate information (either intentionally or unintentionally). An example is the deletion of important information by employees of drug companies in order to minimize the perceived risk of their drugs.…”
mentioning
confidence: 99%
“…Similarly, in [11] a research team analyzed 80 Wikipedia articles on drugs. They found that the articles often missed important information and a small number of factual errors.…”
Section: Comparative Reliability Studiesmentioning
confidence: 99%
“…In most prior work, the "golden standard" for information quality is the evaluations of experts [31,7,5,11]. This standard has a clear advantage: it is as objective, as it gets.…”
Section: Qualitymentioning
confidence: 99%